Design and simulation of a prototype of a small-scale solar CHP system based on evacuated flat-plate solar collectors and Organic Rankine Cycle. (15th January 2015) - Calise, Francesco; d'Accadia, Massimo Dentice; Vicidomini, Maria; Scarpellino, Marco
Highlights: A novel small scale solar power plant was designed and simulated. The system is based on evacuated solar thermal collectors and an ORC system. An average electric efficiency of 10% was found for the ORC. The efficiency of solar collectors was found to be high in summer (>50%). Pay-back periods lower than 5 years were estimated, in case of public funding. Abstract: This paper presents a dynamic simulation model of a novel prototype of a 6 kWe solar power plant. The system is based on the coupling of innovative solar thermal collectors with a small Organic Rankine Cycle (ORC), simultaneously producing electric energy and low temperature heat. The novelty of the proposed system lies in the solar collector field, which is based on stationary evacuated flat-plate solar thermal collectors capable to achieve the operating temperatures typical of the concentrating solar thermal collectors. The solar field consists of about 73.5 m 2 of flat-plate evacuated solar collectors, heating a diathermic oil up to a maximum temperature of 230 °C. A diathermic oil storage tank is employed in order to mitigate the fluctuations due to the variability of solar energy availability. The hot diathermic oil exiting from the tank passes through an auxiliary gas-fired burner which provides eventual additional thermal energy. The inlet temperature of the diathermic oil entering the ORC system varies as a function of the availability of solar energy, also determining an oscillating response of the ORC. The ORC was simulated in Engineering Equation Solver (EES), using zero-dimensional energy and mass balances. The ORC model was subsequently implemented in a more general TRNSYS model, including all the remaining components of the system. The model was used to evaluate the energy and economic performance of the solar CHP system under analysis, in different climatic conditions. The results show that the efficiency of the ORC does not significantly vary during the year, remaining always close to 10%. On the other hand, the efficiency of the solar collectors is very high in summer (>50%) and significantly lower during the coldest winter days (down to 20%). Pay-back periods are extremely attractive in case of feed-in tariffs (about 5 years), whereas the profitability of the system is scarce when no public funding is available. A sensitivity analysis was also performed, in order to determine the combination of system/design parameters able to maximize the thermo-economic performance of the system. It was found that the system may be economically feasible for the majority of locations in the Mediterranean area (pay-back periods around 10 years), whereas the profitability is unsatisfactory for Central-Europe sites.